Rhian Samuel's "the therapy of Moonlight, no.1 from a Garland for Anne": a performance practice / Puteri Sarah Mahzan - Mahzan, Puteri Sarah (2023)
The main goal of this thesis is to learn more about how Rhian Samuel plays and interprets piano music, especially how to play expressively and show her ideas. This thesis is a comparative study of how Rhian Samuel's intentions and thoughts are illustrated in the composition The Therapy of Moonlight, No. 1 from A Garland for Anne and how those devices are illustrated in the movement and executed in performance. This thesis will examine the ideas of tradition and personality in Rhian Samuel's performances based on the piano and the pedagogical principles in Rhian's writings and compositions. It will do this by doing a detailed analysis of the scores. Through this thesis, pianists can use different means of interpretation to interpret the differences between these styles. Music contains solemn emotional expressions that can represent the typical style of 21stcentury classical music. Few pianists and teachers knew about Rhian Samuel's playing background, but it is sometimes clear why they thought this. Because of a lack of documentation about Samuel, these pianists have never heard of Rhian Samuel. To illustrate parallels and contrasts in pianistic performance, I will analyse how to play Rhian Samuel's composition in terms of pace and dynamics.